Efeito do inseticida organofosforado metilparation (Folisuper 600BR) sobre a função cardio-respiratória do peixe teleósteo matrinxã, Brycon cephalus - Olle, Claudio Dalle (2007)
Methyl parathion (MP) is an organophosphorus insecticide used worldwide in agriculture and aquaculture due to its high activity against a broad spectrum of insect pests. In a first phase of the study, specimens of matrinxã (Brycon cephalus) were exposed to a sublethal concentration (2 mg.L-1, 1/3 of the 96h-LC50) of MP (Folisuper 600®, MP 600 g.L-1) for 96h, and their heart rate (fH), oxygen consumption ( 2 O V& ), gill ventilation ( G V& ), and oxygen extraction (EO2) were measured, during normoxia and in response to graded hypoxia. The fish developed a significant bradycardia during moderate hypoxia, which was higher for the MP exposed group. 2 O V& was kept constant over a wide range of O2 tensions of inspired water (PiO2), until he critical oxygen tensions (PcO2), 35 mmHg for control group and 52 mmHg for the MP exposed group, respectively, were achieved. G V& increased following the changes in 2 O V& and was the result of an accentuated increase in breath volume, rather than in breath frequency. Oxygen extraction was kept almost constant at about 56% for both experimental groups, regardless of ambient oxygen tensions or MP exposure. We used an isometric muscle preparation to test the effect of a single 96h MP exposure to 2 mg.L-1 of MP on the heart excitation-contraction coupling of B. cephalus. Ryanodine (a blocker of sarcoplasmic reticulum Ca2+ release) reduced the force of contraction by approximately 70% in B. cephalus ventricle, suggesting that this species utilizes the intracellular Ca2+ storages of the sarcoplasmic reticulum (SR) during routine contractions. MP exposure resulted in a significant decrease in force development and an increase in the time to half relaxation (THR), providing evidences of the effect of MP on intracellular Ca2+ stores. Cardio-respiratory responses to MP can be attributed to damage caused to the gill epithelium, which results in impaired gas exchange. Effects of MP exposure to the ventricular myocardium correspond to the SR Ca2+ storages impairment and to cholinesterase inhibition in nerves supplying the heart.